2005
DOI: 10.1007/s00330-005-2671-7
|View full text |Cite
|
Sign up to set email alerts
|

Disseminated dendriform pulmonary ossification associated with usual interstitial pneumonia: incidence and thin-section CT–pathologic correlation

Abstract: The aim of this work was to assess the incidence of disseminated pulmonary dendriform ossification in usual interstitial pneumonia and nonspecific interstitial pneumonia, and to correlate thin-section computed tomography (CT) and histopathologic findings. We retrospectively reviewed thin-section CT and pathologic specimens of biopsy-proven usual interstitial pneumonia (75 patients, 57 men and 18 women, mean age 60 years, range 29-83 years) and nonspecific interstitial pneumonia (44 patients, 9 men and 35 women… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(39 citation statements)
references
References 11 publications
2
36
0
1
Order By: Relevance
“…Chest CT has a high diagnostic yield for pulmonary ossification. Kim et al 16 evaluated the incidence of dendriform pulmonary ossification in usual interstitial pneumonia. In this study, 75 subjects were diagnosed with usual interstitial pneumonia by chest CT and open lung biopsy: 5 subjects presented with dendriform pulmonary ossification.…”
Section: Discussionmentioning
confidence: 99%
“…Chest CT has a high diagnostic yield for pulmonary ossification. Kim et al 16 evaluated the incidence of dendriform pulmonary ossification in usual interstitial pneumonia. In this study, 75 subjects were diagnosed with usual interstitial pneumonia by chest CT and open lung biopsy: 5 subjects presented with dendriform pulmonary ossification.…”
Section: Discussionmentioning
confidence: 99%
“…Definition of DPO.-Because no radiologic definition for the entity of DPO exists (3,11,14,26), we selected two definitions in line with previous descriptions of "bilateral, multiple tiny ossifications or bony nodules," constructed with ease of application in mind. Definition 1 was one or more ossifications that appear bilaterally, with a total of at least 10.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…DPO has been reported in various contexts, including in patients with normal lungs (idiopathic DPO) (4,5); in those with preexisting cardiac diseases, particularly pulmonary congestion secondary to mitral stenosis (6,7); after severe lung injury (8,9); and in association with fibrosing interstitial lung disease (ILD) (10)(11)(12)(13)(14)(15). Previous studies of DPO have been limited by small patient numbers (11,14) or have been based on autopsy studies (1,16) and thus do not provide a clear idea of the frequency of ossification in fibrosing ILDs or its associations. The aims of our study were to determine the prevalence of DPO in patients with different types of fibrosing ILD and to determine whether there are differences among them.…”
Section: Advances In Knowledgementioning
confidence: 99%
“…One study found this appearance on HRCT in 5 out of 75 patients with UIP; this corresponded histopathologically to multiple dendriform nodules of mature bone embedded in fibrous stroma in basal, subpleural areas of fibrosis and honeycombing [82]. None of 44 patients with NSIP had HRCT or histopathological evidence of pulmonary ossification, and the authors suggest that, in the context of fibrotic lung disease, HRCT appearances compatible with disseminated dendriform pulmonary ossification may help distinguish UIP from NSIP [82].…”
Section: Disseminated Dendriform Pulmonary Ossificationmentioning
confidence: 99%